2008
DOI: 10.1016/j.biopsych.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Genes Controlling Affiliative Behavior as Candidate Genes for Autism

Abstract: Background-Autism Spectrum Disorders (ASD) are neurodevelopmental disorders of complex etiology, with a recognized substantial contribution of heterogeneous genetic factors; one of the core features of ASD is a lack of affiliative behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 57 publications
6
126
3
1
Order By: Relevance
“…These were reported to be associated with ASD in the previous studies. [20][21][22][23] Thus, a total of 12 SNPs were selected. All SNPs were genotyped by using TaqMan genotyping platform.…”
Section: Genotyping and Selection Of The Snpsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were reported to be associated with ASD in the previous studies. [20][21][22][23] Thus, a total of 12 SNPs were selected. All SNPs were genotyped by using TaqMan genotyping platform.…”
Section: Genotyping and Selection Of The Snpsmentioning
confidence: 99%
“…Lerer et al 22 found an association of a haplotype comprising rs22254298 and four other SNPs (rs237897-rs13316193-rs237889-rs2254298-rs2268494) with ASD, but as a single SNP, rs2254298 was not associated with ASD (Lerer et al 22 ). Yrigollen et al 23 found that rs2268490, which was in the same haploblock of rs2254298, was associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, significant association between OXTR SNPs [21][22][23][24][25][26] and risk for autism has been provisionally shown (but also see [27,28]) and, notably, was mediated by socialization skills in our study [23]. Additionally, SNPs associated with ASD are also associated with amygdala volume [29], depression/anxiety [29], negative emotionality [30], attention deficit [31], adult attachment styles [32,33] (but see [34]), affectivity, emotional loneliness and IQ [35], empathy and stress reactivity [36], observed parenting [37], with sexual phenotypes [38] and in our own studies with prosocial behavior [39].…”
Section: Oxytocin and Autism Spectrum Disorders (Asd)mentioning
confidence: 99%
“…As regards this latter pathway, decreased circulating oxytocin levels in individuals with ASD has been observed (Modahl et al, 1998), and administration of oxytocin to individuals with ASD has been reported to reduce repetitive behaviors (Hollander et al, 2003), enhance retention of social cognition (Hollander et al, 2007) and improve emotional recognition (Guastella et al, 2010). Furthermore, OXTR, which is located at chromosome 3p25 and encodes a G-protein coupled receptor, has been associated with ASD in numerous studies (Wu et al, 2005;Ylisaukko-oja et al, 2006;Jacob et al, 2007;Lerer et al, 2008;Yrigollen et al, 2008;Gregory et al, 2009;Liu et al, 2010;Wermter et al, 2010).…”
Section: The Oxytocin System In Asd and Its Interactions With Other Pmentioning
confidence: 99%